Hot electron and x-ray generation by sub-ns kJ-class laser-produced tantalum plasma. (1st October 2022) - Singh, Sushil; Krupka, Michal; Istokskaia, Valeria; Krasa, Josef; Giuffrida, Lorenzo; Dudzak, Roman; Dostal, Jan; Burian, Tomas; Versaci, Roberto; Margarone, Daniele; Pisarczyk, Tadeusz; Krus, Miroslav; et al.
Abstract: This paper presents experimental investigation of temperature scaling and threshold of instability in hot electron and bremsstrahlung radiation from the interaction of sub-nanosecond and kilo-joule class laser pulses with a tantalum foil target at Prague Asterix Laser System. The laser intensity was varied between 4 × 10 15 and 3 × 10 16 W · cm −2 at the target focus. The energy distribution functions of electrons were measured by an angular array of magnetic spectrometers indicating the electron temperature in the range between 30 keV and 70 keV. The bremsstrahlung spectrum was characterized using a scintillator-based calorimeter. In particular, we show the laser-energy scaling of the total flux of hot electrons in the forward and backward directions with respect to the laser vector, the conversion efficiency of the laser energy to the energy carried by hot electrons, and the temperature of hot electrons as well as the unfolded bremsstrahlung temperature using a Monte Carlo code consistent with signals of the scintillator detector. The scaling shows that the electron flux increases discontinuously with increasing laser intensity from ∼ 1 − 2 × 10 16 W · cm −2 with consequent instability in the production of hot electrons and bremsstrahlung radiation.